2011
DOI: 10.1007/s00122-011-1700-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL controlling maize deep-seeding tolerance-related traits and confirmation of a major QTL for mesocotyl length

Abstract: Deep-seeding tolerant seeds can emerge from deep soil where the moisture is suitable for seed germination. Breeding deep-seeding tolerant cultivars is becoming increasingly important in arid and semi-arid regions. To dissect the quantitative trait loci (QTL) controlling deep-seeding tolerance traits, we selected a tolerant maize inbred line 3681-4 and crossed it with the elite inbred line-X178 to generate an F(2) population and the derivative F(2:3) families. A molecular linkage map composed of 179 molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 38 publications
5
36
0
Order By: Relevance
“…Furthermore, total 11 clusters were found across both growing conditions and overlapping QTL loci were consistent with significant correlations between different germination-related traits (Supplementary Table 3). Similar results were obtained in previous studies (Tommasini et al, 2008; Zhao et al, 2010; Zhang et al, 2012). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, total 11 clusters were found across both growing conditions and overlapping QTL loci were consistent with significant correlations between different germination-related traits (Supplementary Table 3). Similar results were obtained in previous studies (Tommasini et al, 2008; Zhao et al, 2010; Zhang et al, 2012). …”
Section: Discussionsupporting
confidence: 92%
“…In contrast, one QTL for mesocotyl length ( qSGML6-1 ) was found to locate near the centromere of chromosome 6 under the standard-germination condition. Recent studies at two sowing depths of 10 and 20 cm revealed 25 QTL for four traits including mesocotyl length, coleoptile length, seedling length, and germination rate in two parents of X178 and 3681-4 (Zhang et al, 2012). However, no QTL was found on chromosome 5 or 9, contrary to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly demonstrated the existence of QTLs controlling mesocotyl elongation on chromosomes 1 and 3. Previous studies identified a QTL for mesocotyl length in a putatively homeologous location on the long arm of maize chomosome 3 (Troyer [1997]; Zhang et al [2012]). Troyer ([1997]) found three regions on chromosome 3, 6 and 9 related to mesocotyl elongation using translocation tester stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Troyer ([1997]) found three regions on chromosome 3, 6 and 9 related to mesocotyl elongation using translocation tester stocks. Three QTLs for mesocotyl length were commonly detected on chromosome 1, 3 and 10 under two different sowing depth conditions in maize (Zhang et al [2012]). While the resolution of the maize QTL was low, the positional correspondence raises the possibility that this locus may be involved in controlling mesocotyl length in both rice and maize (Wei et al [2007]; Soderlund et al [2011]http://www.symapdb.org).…”
Section: Discussionmentioning
confidence: 99%